Advanced technologies on the sustainable approaches for conversion of organic waste to valuable bioproducts: Emerging circular bioeconomy perspective. (15th September 2022) - Ashokkumar, Veeramuthu; Flora, G.; Venkatkarthick, Radhakrishnan; SenthilKannan, K.; Kuppam, Chandrasekhar; Mary Stephy, G.; Kamyab, Hesam; Chen, Wei-Hsin; Thomas, Jibu; Ngamcharussrivichai, Chawalit
Graphical abstract: Highlights: Waste disposal and its hazardous impact on health and the environment. Latest technologies for converting the organic waste to multiple biofuels production. Organic acids, bioplastic, and bio-compost production from organic waste. Described the techno-economic analysis for organic waste. Abstract: Rapid population growth and other human activities have generated massive waste from various sectors in recent decades. Studies revealed that by 2050, global solid waste generation is expected to reach 70% to 3.4 billion metric tons. Thus, the authorities urgently need to provide a low-cost, efficient technology for treating waste disposal. However, it is evident that only 20% of waste is recycled, and the remaining is still being considered for landfilling. In developing countries, the generated waste is simply disposed of in an open area, which causes a severe threat to humans, animals, and the environment. To date, organic waste and fourth-generation biomass have been investigated for multiple targeted products. Thus, the present review article highlights the emerging problems in organic waste generation, management, and converting them into various value-added bioproducts. This review also deals with the conversion of multiple biofuels such as liquid, solid, gaseous, and bioelectricity from organic waste resources. Besides, the latest approaches in organic waste are also detailly addressed for the production of value-added bioproducts such as bioplastic, bio-compost, and organic acids. Furthermore, the techno-economic analysis (TEA) and life cycle assessment (LCA) of organic waste is also explored. The transformation of organic waste to value-added bioproducts enhances the circular bioeconomy approach by reducing waste, increasing energy production, and other healthcare products. Finally, it is concluded that the utilization of organic waste to value-added bioproducts and biofuels production will be helpful in achieving high energy security, environmental protection, as well as enhancing the bioeconomy perspective.